Thymol synthesis via alkylation of m-cresol with isopropanol the effect of the SiO2/AI2O3 ratio of H-MFI catalysts on catalyst activity and thymol selectivity - Nagooroo, Sancha (Department of Chemical Engineering, 2015)
Includes bibliographical references.